(untitled) (Research, Society and Development, 2022)
A large percentage of patients who present themselves to dental professionals are carriers of dentofacial deformities that fit into the Angle Class II pattern but are unaware of or have never been informed of their alterations. This can be explained by the lack of knowledge by professionals about the dental occlusion patterns, as well as the correct treatment indications for such problems or the indication of surgery only associated with aesthetic factors. This paper provides an analysis of this problem, showing other criteria, not only aesthetic, for the indication of orthognathic surgery in patients with dentofacial deformities, classified as Angle’s class II, based on aesthetic, morphofunctional and semiological principles, with the purpose of showing that surgeries are viable alternatives for the correction of these deformities. This study fits the research design, descriptive literature review with integrative and qualitative-exploratory analysis based on the main research platforms, searching for the terms: "Orthognatic Surgery, Angle Class II", "Orthognathic surgery in class II patients", " angle class II surgical correction". The time interval was from 2012 to 2022 in English, Portuguese and Spanish language with a n of 13 articles. It was clear that orthognathic surgery is a very valid tool in the correction of Angle class II deformities, since the procedure brings improvements in the morphological, physiological and psychosocial conditions of the individuals who choose to do so.